Comparative morphological, sensory and Gas Chromatography-Mass Spectrometry evaluation of three Jasminum auriculatum genotypes for floriculture and perfumery applications - Priyatharsini, A; Ganga, M; Keerthivasan, R; Thamaraiselvi, S P; Manikanda, B N; Manonmani, S; Santhanakrishnan, V P (Plant Science Today, 2026)
Integrated comparative studies combining morphology, sensory attributes and aroma profiling in Jasminum auriculatum genotypes are limited, hindering the identification of superior types for commercial and perfumery use. The current study aimed to evaluate the morphophysiological traits, floral quality and aroma profile of three J. auriculatum genotypes, CO.2 Mullai, Muthu Mullai and Pacha Mullai to identify superior types for commercial cultivation and perfumery applications. The field experiment was conducted at the Department of Floriculture and Landscape Architecture, Tamil Nadu Agricultural University (TNAU), Coimbatore, during 2023–2025, using a randomized block design (RBD) with five replications. All vegetative and floral parameters showed significant genetic variability. Among the genotypes, CO.2 Mullai recorded the maximum height (157.5 cm), longest buds (3.11 cm), highest flower yield (FY) (2437.6 g plant-1) and the highest concrete recovery (0.287 %), proving to be the best. As part of the sensory evaluation using a nine-point hedonic scale, CO.2 Mullai achieved the highest total acceptability (mean score = 2.17), mainly owing to its strong, pleasant scent. Gas Chromatography-Mass Spectrometry analysis revealed 19 volatile compounds across different genotypes, with CO.2 Mullai showing linalool (3.62 %), caryophyllene (5.51 %) and acetic acid methyl ester (12.98 %) as the main contributors to its floral scent. Muthu Mullai had more α-farnesene (6.26 %) and linalool (4.82 %), while Pacha Mullai exhibited the highest acetic acid methyl ester (30.21 %) content. The combination of morphological, sensory and metabolite data led to the conclusion that CO.2 Mullai was the genotype with the highest FY, fragrance quality and concrete recovery. However, Pacha Mullai remains noteworthy for its green buds and distinct floral scent, which hold emerging market appeal.